2022
DOI: 10.1186/s13047-022-00600-0
|View full text |Cite
|
Sign up to set email alerts
|

Does in‐shoe pressure analysis to assess and modify medical grade footwear improve patient adherence and understanding? A mixed methods study

Abstract: Background Medical grade footwear (MGF) with demonstrated plantar-pressure reducing effect is recommended to reduce the risk of diabetes-related foot ulceration (DFU). Efficacy of MGF relies on high adherence (≥ 80%). In-shoe pressure analysis (IPA) is used to assess and modify MGF, however, there is limited evidence for the impact on patient adherence and understanding of MGF. The primary aim of this study was to determine if self-reported adherence to MGF usage in patients with previous DFU i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…As we noted in our previous guideline, 16 adherence to an intervention has been shown to be crucial in preventing foot ulcers, and it is consistently reported that people with diabetes who do not adhere present with higher rates of ulceration 9 . Several studies have investigated methods to improve adherence, 36,70,71 but a stronger focus on the development, evaluation and implementation of methods that improve adherence to preventative foot treatment remains urgently needed. In turn, evaluating and optimising feasibility and acceptability of treatments for people with diabetes, should be a key priority in the ongoing development and clinical research on the prevention of diabetes‐related foot ulceration. Probably the three most common preventative actions in daily clinical foot practice globally are foot screening (recommendations 1 and 2), foot self‐care (recommendations 3 and 4), and (structured) education (recommendation 5).…”
Section: Considerationsmentioning
confidence: 93%
See 1 more Smart Citation
“…As we noted in our previous guideline, 16 adherence to an intervention has been shown to be crucial in preventing foot ulcers, and it is consistently reported that people with diabetes who do not adhere present with higher rates of ulceration 9 . Several studies have investigated methods to improve adherence, 36,70,71 but a stronger focus on the development, evaluation and implementation of methods that improve adherence to preventative foot treatment remains urgently needed. In turn, evaluating and optimising feasibility and acceptability of treatments for people with diabetes, should be a key priority in the ongoing development and clinical research on the prevention of diabetes‐related foot ulceration. Probably the three most common preventative actions in daily clinical foot practice globally are foot screening (recommendations 1 and 2), foot self‐care (recommendations 3 and 4), and (structured) education (recommendation 5).…”
Section: Considerationsmentioning
confidence: 93%
“…As we noted in our previous guideline, 16 adherence to an intervention has been shown to be crucial in preventing foot ulcers, and it is consistently reported that people with diabetes who do not adhere present with higher rates of ulceration. 9 Several studies have investigated methods to improve adherence, 36,70,71 More research in this area is needed.…”
Section: Considerationsmentioning
confidence: 99%